La ciudadanía corporativa como inversión en capital social. Creación de alianzas entre empresa y sociedad (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
This article provides a theoretical foundation for corporate social responsability and corporate citizenship, making use of the concept of  Social Capital’. It is argued that enterprises often feel and act as members of their local communities. Bussiness has an interest in the solution of local problems. Therefore business enterprises could become an important actor in collective problem solving on a regional or branch level. Furthermore, it would in many ways gain from networks of cooperation. This article sketches the social case as well as the business case of those ‘investments in Social Capital’.